Art at the Airport - Van Jole, Marcel; Claes, Theo; Zimmerman, Yonah; Van Buynder, Ernest (Brussel : BIAC, 2002)
Aguirre Y Otegui, Philip ; Alechinsky, Pierre ; Baudart, Johan ; Beaumont, Hanneke ; Bitker, Colette ; Bosquet, Yves ; Cordier, Pierre ; Coster, Jocelyne ; Da Ponte, Carlos ; De Beul, Bert ; De Bodt, Anne ; De Koninck, Jaak ; De Maeyer, Jacky ; De Wit, Gaspard ; Decelle, PHilippe et al.
boek